2019
DOI: 10.1111/iej.13145
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological, histoenzymological, immunohistochemical and immunofluorescence analysis of tissue response to sealing materials after furcation perforation

Abstract: Aim To evaluate in vivo tissue responses after sealing furcation perforations in dog's teeth with either Biodentine™, mineral trioxide aggregate (MTA) or gutta‐percha, by means of histopathological, histoenzymological, immunohistochemical and immunofluorescence analysis. Methodology After root canal treatment, perforations were created in the central region of the pulp chamber floor using a round diamond bur and filled with one or other of the materials. The animals were euthanized after 120 days, and the teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This could suggest a reaction to the implantation of BD, indicating its mineralizing potential, as in cytokine measurements in the present study, this material significantly expressed IL‐8 at 30 days and also expressed mRNA of BMP2 in the same period. As for MTA and BMP2, our study confirmed the findings of Önay et al, 27 but Silva et al 28 showed that MTA stimulates BMP2 expression. This suggests that these affinities could result from the close relationship of BMPs with osteoblasts, where both BMP2 and BMP4 have effects on osteoblasts, 73 making it difficult to elucidate the specific roles during osteogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could suggest a reaction to the implantation of BD, indicating its mineralizing potential, as in cytokine measurements in the present study, this material significantly expressed IL‐8 at 30 days and also expressed mRNA of BMP2 in the same period. As for MTA and BMP2, our study confirmed the findings of Önay et al, 27 but Silva et al 28 showed that MTA stimulates BMP2 expression. This suggests that these affinities could result from the close relationship of BMPs with osteoblasts, where both BMP2 and BMP4 have effects on osteoblasts, 73 making it difficult to elucidate the specific roles during osteogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, only one study to date has assessed the relationship between BMP4 and MTA, thus confirming its osteogenic‐odontogenic potential 26 . As for BMP2, a study has demonstrated no relationship between BMP2 and MTA, only in a special formulation known as MM‐MTA 27 ; however, another study has shown that MTA stimulates BMP2 expression 28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their protocols for outcome assessment differed in, for example, observation time points and outcome assessment methods. Many studies assessed these characteristics by means of scores (Aladimi et al, 2020; Al‐Daafas & Al‐Nazhan, 2007; Bakhtiar et al, 2017; Cardoso et al, 2018b; Noetzel et al, 2006; Samiee et al, 2010; Silva et al, 2019; de Sousa Reis et al, 2019) or cell counting (da Fonseca et al, 2019; Hassanien et al, 2015; Neto et al, 2010, 2012; da Silva et al, 2011; Silva et al, 2017; Tawfik et al, 2016). Even those studies that analysed the outcomes by means of scores evaluated different characteristics in each score.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of perforation management is to maintain healthy periodontal tissues adjacent to the perforation without persistent inflammation or loss of periodontal attachment. In the case of established periodontal tissue breakdown, the aim is to re‐establish tissue attachment (Pitt Ford et al, 1995; Silva et al, 2019). Thus, successful perforation repair depends on the ability to seal the perforation and to re‐establish a healthy periodontal ligament (Seltzer et al, 1970).…”
Section: Classification Of Perforations and Factors Affecting Prognosismentioning
confidence: 99%